Two new Alpine Leuctra in the L. braueri species group (Plecoptera, Leuctridae) - Vinçon, Gilles (Illiesia, 2011)
Two new species of the genus Leuctra that were previously confused with L. braueri Kempny, 1898 are described from the eastern Alps: L. muranyii sp. n. and L. juliettae sp. n. A comparative description of L. braueri is given. The composition and characters of the L. braueri species group are discussed.
Keywords: entomologija; entomology; Plecoptera; vrbnice; nove v rste; stonefly; Leuctridae; Leuctra; braueri group; new species; endemics; Italy; Switzerland; Austria